"People Are Enemies to What They Don't Know" Managing Stigma and Anti-Muslim Stereotypes in a Turkish Community Center. (April 2017) - Paul, Crystal; Becker, Sarah
In the wake of the 9/11 terrorist attacks on the World Trade Center, anti-Muslim discourse and sentiment has become pervasive in the West. Using a collaborative ethnographic approach, we observe how participants at a Turkish Community Center (TCC) cultivate stigma management strategies against the cultural backdrop of post-9/11 anti-Muslim stereotypes. In our analysis, we use Goffman's work on stigma and critical race theory to explore the socially embedded nature of stigmatization processes for Turkish Muslims in a local community center. Our findings reveal how aspects of Turkish culture and Islam, together with a structural context that facilitates collective stigma management, allow TCC participants to effectively manage stigma and combat anti-Muslim stereotypes. Turkish participants use the practice of "dialogue" to prioritize secular identity(ies) through cultural education, normalize the Muslim self in conversation about religion, and embody a gendered presentation of Islam and Turkish culture. While facilitating individual and collective resilience for TCC participants in the face of stigmatization and pervasive anti-Muslim sentiment, these practices also contribute to the reproduction of broader patterns of racial, cultural, and gender inequality.